Human pseudomyiasis caused by Eristalis tenax (Linnaeus) (Diptera: Syrphidae) in Goiás Pseudomiíase humana causada por Eristalis tenax (Linnaeus) (Diptera: Syrphidae) em Goiás - Marco Tulio A. Garcia-Zapata; Edson Sidião de Souza Júnior; Fernando Freitas Fernandes; Sônia F.O. Santos (Revista da Sociedade Brasileira de Medicina Tropical, 2005)
The objective of the present work was to register the first proven cases of human pseudomyiasis due to Eristalis tenax in Goiás State, Brazil, underscoring their clinical manifestations and direct relationship with hygiene. The taxonomic identification of the instars was done according to the descriptions and keys presented by James (1947), Hartley (1961) and Guimarães & Papavero (1999). Two cases were observed. In both cases there was no evidence of apparent mental disturbance. The clinical picture of these cases was self limited. The water supply, sewer system, socioeconomic level and habits of the suspect species of the flies are criteria that should be investigated. O presente trabalho visa registrar os primeiros casos evidenciados de pseudomiíases humanos por Eristalis tenax no estado de Goiás, Brasil, destacando suas manifestações clínicas e suas relações diretas com os hábitos higiênicos. A identificação taxonômica das larvas foi realizada com base nas descrições e chaves apresentadas por James (1947), Hartley (1961) e Guimarães & Papavero (1999). Observaram-se dois casos. Em ambos não havia evidência de pertubações mentais claras. O quadro clínico de ambos os casos era mesmo limitado. O abastecimento de água, o nível sócio-econômico e o hábito das espécies das moscas são critérios que devem ser considerados na investigação.